Psychosocial stress, standing time and overweight are risk factors for pregnancy induced hypertension: A case control study - N Perera; C Abeysena (College of Community Physicians of Sri Lanka, 2011)
Objective: To determine the risk factors for pregnancy induced hypertension (PIH). Methods: This was a case control study, carried out at Castle Street Hospital for Women during August to September 2006. Hundred mothers newly diagnosed as having PIH were chosen as cases and 100 mothers with uncomplicated pregnancies as controls. Both cases and controls had a period of amenorrhoea of >20 weeks. Psychosocial stress was measured using General Health Questionnaire 30 (GHQ) and the Modified Life Event Inventory (MLEI). Maternal socio-demographic information and other data were collected using an interviewer administered questionnaire and a record sheet. Multivariate logistic regression analysis was applied to control for confounders and the results were expressed as odds ratios (OR) and 95% confidence intervals (95%CI). Results : After adjusting for confounding effect experience of ³2 life events during pregnancy (OR:2.1, 95%CI:1.06–10.9), a maternal BMI of ³25 kg/m2 (OR:2.4, 95%CI:1.1–5.0), maternal age of ³28 years (OR:3.9, 95%C.I:2.0–7.5), history of ante partum haemorrhage (OR:3.4, 95%CI:1.1–10.9) and standing for >1.5 hours at one stretch (OR:3.4, 95%CI:1.6– 7.4) had statistically significant associations with developing PIH. Conclusions: Psychosocial stress during pregnancy, being an overweight or obese women, age ³28 years, history of antepartum haemorrhage and standing ³1.5 hours at one stretch were risk factors for PIH. Key words case control study; hypertension; life change events; pregnancy; risk factors; stress   DOI: http://dx.doi.org/10.4038/jccpsl.v16i1.3870 Journal of the College of Community Physicians of Sri Lanka Vol.16(1) 2011, p35-39